Professional learning in the knowledge society - Lahn, Leif Chr; Nerland, Monika (The Knowledge Economy and Education ;, 2012)
This book presents an entirely new approach to professional learning based on perspectives of the knowledge society and, in particular, an interpretation of Knorr Cetina's work on scientific 'epistemic cultures'. Starting with a conceptual chapter and followed by a suite of empirical studies from accountancy, education, nursing and software engineering, the book elaborates how: a) knowledge production and circulation take distinct forms in those fields; b) how the knowledge objects of practice in those fields engross and engage professionals and, in the process, people and knowledge are transformed by this engagement. By foregrounding an explicit concern for the role of knowledge in professional learning, the book goes much farther than the current fashion for describing 'practice-based learning'. It will therefore be of considerable interest to the research, policy, practitioner and student communities involved with professional education/learning or interested in innovation and knowledge development in the professions.